1991
DOI: 10.1177/036354659101900211
|View full text |Cite
|
Sign up to set email alerts
|

The long-term course after treatment of acute anterior cruciate ligament ruptures

Abstract: Acute total ACL (N = 60) and concomitant medial collateral ligament (N = 46) ruptures were repaired in 60 patients (mean age, 28 years) without augmentation. Menisci were removed in 23 knees. Fifty-three (88%) of the patients were reexamined 9 to 16 years later with special emphasis on manual and instrumented stability testing (Stryker, Genucom), knee function score (Lysholm), and activity level (Tegner). Standing roentgenograms (30 degrees of knee flexion) were taken in 69% of the patients. At followup, an AC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
96
0
2

Year Published

1994
1994
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 185 publications
(104 citation statements)
references
References 55 publications
6
96
0
2
Order By: Relevance
“…However, we found no correlation between instability and OA. Similar conclusions were reached by Sommerlath et al [3] and Gillquist and Messner [2].…”
supporting
confidence: 86%
See 1 more Smart Citation
“…However, we found no correlation between instability and OA. Similar conclusions were reached by Sommerlath et al [3] and Gillquist and Messner [2].…”
supporting
confidence: 86%
“…However, we found no correlation between instability and OA. Similar conclusions were reached by Sommerlath et al [3] and Gillquist and Messner [2].Roe et al [4] reported that ACL reconstruction patients with PT autograft showed higher OA incidence than those with hamstring autograft. However in our study we used a patellar tendon autograft in all cases and we have provided no information about the relationship between OA and graf t choice (PT or hamstring).…”
supporting
confidence: 74%
“…The occurrence of repeated sprains resulting from an anterior instability of the knee usually leads to meniscal and chondral injuries. The dissatisfaction of the individuals with their knees' performance motivates surgical treatment to recover stability (3)(4)(5)(6) . However, there is no consensus about the number of patients that will show instability or future degenerative changes.…”
Section: Discussionmentioning
confidence: 99%
“…The natural progression of this ligament injury remains unclear, but it is believed that the anterior instability may evolve to meniscal and chondral degenerative injuries (3)(4)(5) and the natural evolution is reflected on the performance of these individuals in their physical activities (6) . In the USA, the annual incidence is estimated as 0.35 ACL injury/ general population resident, resulting in approximately 75,000 injuries each year (7) .…”
Section: Introductionmentioning
confidence: 99%
“…4 Patients with rupture of the anterior cruciate ligament (ACL) develop posttraumatic OA of the knee. 5 Restoration of knee stability by reconstruction provides symptomatic relief, but does not decrease the incidence of degenerative changes of the ACL injured knee. 6 This suggests that the development of posttraumatic OA may not have a purely biomechanical origin, and that chemical changes may also be involved.…”
Section: Introductionmentioning
confidence: 99%